(untitled) (Perner’s Contacts, 2012)
The paper deals with questions of fare collection systems in the frame of integrated public passenger transport system as well as with requirements and standards of fare collection systems. The relations between fare collection system and tariff system, information and sale (distribution) systems are also mentioned next to it. Brief proposal of application of these fare collection systems in the frame of integrated public passenger transport systems by fulfilment of all given conditions placed on these systems is mentioned in the conclusion part of this paper.